Transcreación musical: transgresión de agencias para la investigación artística - Susana Castro Gil (2022)
The present thesis is a partial piece of artistic research that seeks to link artistic practice and reflexive-philosophical research in a project interested in the creative agency of the performer in the context of Western art-music. The main objective of this doctorate is to carry out through musical performance an inquisitive reflection on the scale of values that determines what is called a good performer, i.e., a virtuoso - having as a subsidy the etymology of the word that qualifies the virtuoso as a subject of value or quality -. This in order to propose a mythopoetic reconfiguration of the good performer in contemporaneity based on the application of Haroldo de Campos' theory of transcreation, which implies the acceptance of the co-creative role of the performer in the musical process. Starting from the possibility of establishing parallels between the agency of the translator and the musical performer of western music-art, this thesis conveys the theory of transcreation of poetic texts to the field of musical performance with the aim of offering a ground for reflection that founds a practice in which the performer assumes a co-creative role of the musical work, deriving in a performative practice that recognizes the active action of the performer as a co-formative agent of the aesthetic matter of the work. Likewise, influenced by the philosophical thought of Luigi Pareyson and Paulo de Assis, this work addresses the ontology of the musical work as a regulatory principle of the practice and proposes the acceptance of an ontology that crumbles the conception of concluded and absolute work, defending the idea of musical work as multiplicity that instigates the transcreative performance that, through transtemporal synchronization and intertextual dialogue, proposes re-formations of the works. At the same time, questions are raised about the authenticity and ethics of the performative action in force in the context of Western art-music, the conservative habitus, assuming that ethics is a mobile contingent that varies as societies change and the motivations of the individual performer change. This exercise of critique through performance is approached from creative multimedia gestures that mobilize a reading of a selection of piano etudes from piano technique books Gradus ad Parnassum that are put in intertextual dialogue with contemporary media and aesthetics. In addition to the presentation of the written thesis, this PhD project includes the formulation of a series of experimental multimedia performances where the transcreations of the piano etudes are projected live and the creation of a randomly navigated virtual exhibition hosted on the Research Catalogue website in which the results of the creative processes are arranged so that virtual visitors have access to the transcreations of the etudes, philosophical reflections and evidence of the unfolding of this research.